THE BODY MANIFESTATIONS IN CULTURE HIP-HOP (Fiep Bulletin - online, 2013)
This work presents an analysis of corporeality, whose objective is to identify what corporal manifestations in the culture of the movement hip-hop, linking the elements of the movement with the speeches of Members active. It is concluded that the demonstrations in body movement hip-hop express not only by break, it is the element dance, but also in the other three, as well as was found a fifth element corporal in movement hip-hop, being the citizenship, where the body is create awareness of their role in society.
Keywords: Body; culture; hip-hop.